Ferrous fumarate nanoliposomes: Formulation, characterization, and diffusion profiles - Arman Suryani, Marlyn Dian Laksitorini, Teuku Nanda Saifullah Sulaiman (Journal of Applied Pharmaceutical Science, 2024)
To assess the effect of cholesterol concentration in the preparation of ferrous fumarate nanoliposome toward its physicochemical properties and stability. Nanoliposomes were produced with cholesterol concentrations of 8, 12, and 16 mg using the thin film hydration method. The ultrasonic dispersion method and mini extruders were used to reduce the particle size. The nanoliposomes were evaluated for their physical properties, encapsulation efficiency, stability, and transport in the in vitro model of skin absorption. Formula 3 showed the smallest size results, with spherical multilamellar vesicle globules with a relatively dense matrix structure and even distribution between particles with a positive zeta potential value with an encapsulation efficiency percentage value of 61.67% ± 0.50 and a cumulative amount penetrated at the second hour of 442.077 mcg/cm2 ± 17.270 with a flux value of 14.575 mcg/cm−2/hour−1. Formulation 3 with higher cholesterol concentration showed better physical characteristics, encapsulation efficiency, and in vitro skin penetration compared to formulations with lower cholesterol concentration.
Keywords: Ferrous fumarate, thin layer hydration, mini extruder, nanoliposomes, cholesterol